Brief Report: Impact of ART on Maternal Health After Cessation of Breastfeeding. (1st April 2021) - Brummel, Sean S.; Taha, Taha E.; Angelidou, Konstantia (Nadia); Saidi, Friday; Atuhaire, Patience; Dula, Dingase; Moodley, Dhayendre; Matubu, Allen; Chareka, Gift; Nevrekar, Neetal; Vhembo, Tichaona; Fairlie, Lee; et al.
Abstract: IMPAACT PROMISE 1077BF/FF was a sequentially randomized study of pregnant and postpartum women living with HIV to investigate the efficacy and safety of antiretroviral therapy (ART). This Maternal Health Component investigated efficacy for the risk of developing AIDS or death; and safety among women randomized to continue ART (CTART: N = 289) or discontinue ART (N = 268) after cessation of breastfeeding or after confirmation of infant infection. No AIDS-defining illnesses were reported during follow-up in either arm. Adverse events of grade 3 or higher were more frequent in the CTART arm [hazard ratio = 1.78, 95% confidence interval: (1.05 to 3.02), P -value = 0.03]. The difference in adverse events in the 2 groups was mostly driven by moderate weight loss for women on the CTART arm.